1978
DOI: 10.1002/1097-4679(197807)34:3<781::aid-jclp2270340343>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Goal choice of alcoholics: A comparison of those who choose total abstinence vs. those who choose responsible, controlled drinking

Abstract: Examined possible pre-treatment differences between alcoholic veterans who choose total abstinence and those who choose responsible drinking as their drinking goal. The two groups were compared on a variety of behavioral, cognitive, affective, and demographic characteristics. It was found that those who choose responsible drinking had a significantly shorter history of abusive drinking (6.5 years vs. 11.5 years) and more education (12.5 years vs. 10.8 years). In addition, the responsible drinking group showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…A strong association between the initial preferred drinking goal and successful treatment outcome has been reported (2)(3)(4)(5)(6)(7). Individuals seem to select the goal that best fits their needs and circumstances, which is likely to result in a better outcome.…”
Section: Introductionsupporting
confidence: 81%
“…A strong association between the initial preferred drinking goal and successful treatment outcome has been reported (2)(3)(4)(5)(6)(7). Individuals seem to select the goal that best fits their needs and circumstances, which is likely to result in a better outcome.…”
Section: Introductionsupporting
confidence: 81%
“…While previous studies on this topic exclusively focused on patients with present alcohol use disorders (Adamson & Sellman, 2001;Heather et al, 2010;Pachman, Foy, & Van Erd, 1978) clients in our study were more heterogeneous, including those without alcohol use due to prior detoxification at another institution, as well as clients who reduced their alcohol use prior to treatment admission to a non-hazardous level.…”
Section: Discussionmentioning
confidence: 96%
“…Early work to understand the characteristics associated with goal selection generally found that CD was associated with higher levels of functioning. In a study of veterans receiving inpatient alcohol-dependence treatment, participants who selected abstinence goals had fewer years of education and more years of problem drinking than those with CD goals (Pachman et al, 1978). Comparing those who personally selected a CD or abstinence goal with those who were prescribed abstinence by a provider because of disease severity revealed similar results (Booth et al, 1984).…”
mentioning
confidence: 99%